El complejo gastronómico de Chorrillos: el nuevo mercado de la playa Los Pescadores - Ramos Suarez, David (2022)
During our trips to Europe, we discovered the imposing architecture of the gastronomic markets, traditional and modern, in different cities as key points for all tourists. In this research we will demonstrate the use and great impact that markets can have in the city of Lima, for this particular case, we will show the contribution that the gastronomic compound can provide in the Chorrillos district. Located on the Los Pescadores beach, the beach and the market contribute to revalue the historical and cultural area of the district, thus being one of the most recognized tourist attractions in the same and on the Costa Verde. The problem of the markets in the city of Lima stems from the bad infrastructure, to the bad relationship with the environment. The design proposal will be made taking into account reference projects from world-renowned markets. Finally, the city of Lima has been named as the “Gastronomic Capital of Latin America”. Being the capital and being located on the coast, it has the ideal characteristics so that there is an architecture that honors them, and what better location than on Los Pescadores beach, which respects both. The project becomes a unique place with sufficient potential due to its location, its history, culture, tradition, landscapes and access roads so that Chorrillos and the city of Lima can have a gastronomic compound that generates improvement in the environment and is relevant throughout the South Pacific coast.